Remote test bench system design course of electric vehicle road resistance simulation for high education - Zhang, Caizhi (Technium Electro, 2024)
As an independent curriculum design course, this paper proposes a new remote teaching approach to reinforce students’ ability of combination of theory knowledge and engineering practice by a comprehensive test bench system design. This method is useful during the Coronavirus disease (COVID-19) epidemic where stricter social distancing measure is enforced by local government. The design of this test bench system includes two parts, the hardware structure and the system software，which combine the knowledge of fuel cell, automobile and mechanical design, and integrate LabVIEW programming. The transmission structure of test bench is selected to develop the curriculum design course, which is the foundation for mastering the structure and driveline of vehicle. In addition, a road resistance simulation system which adopts a half-duplex RS-232 bus type communication network and accumulate and check-up communication algorithm is realized by LabVIEW. Data communication and control is an important part of the future development of unmanned vehicle. The design process of software and hardware matching is conducive to shaping students' overall understanding of automobile system and to strengthen their ability to apply 3D modeling, simulation and analysis. At last, the questionnaire analysis showed that the proposed remote practical course design method is useful and advisable.